The glycobiology of the CD system: a dictionary for translating marker designations into glycan/lectin structure and function - Gabius, Hans-Joachim; Kaltner, Herbert; Kopitz, Jürgen; André, Sabine (Trends in biochemical sciences, 2015)
The profile of cell surface molecules, the biochemical platform for cellular communication, can be likened to a molecular fingerprint. Historically, raising monoclonal antibodies by immunization with cells has been instrumental in obtaining tools suited for phenotyping and functional analysis. Initially for leukocyte antigens, the resulting cluster of differentiation (CD) nomenclature has become a popular system for classification. Glycans presented on proteins or lipids and receptors for carbohydrate structures (lectins) are part of the CD list. Our review presents biochemical and biomedical highlights of the respective CD entries.